A cellulose monolith supported metal/organic framework as a hierarchical porous material for a flow reaction. Issue 3 (10th December 2019) - Yang, Zhaohang; Asoh, Taka-Aki; Uyama, Hiroshi
Abstract : A novel cellulose monolith supported ZIF-8 metal organic framework as a hierarchical porous material was designed by using a highly effective pump injection method, which is used for a flow-based reaction. Abstract : A cellulose monolith with immobilized controlled-growth metal organic frameworks (MOFs) is developed. The synthesized hierarchical porous monolith shows great performance as a flow reactor.